MULTIPLE PERSONALITY IN VENOM MOVIE SCRIPT WRITTEN BY JEFF PINKNER ET.AL. - Lazuardi Akbar; Safitri Hariani (JOURNAL OF LANGUAGE, 2021)
This study constitutes an analysis of the Multiple Personalities in Venom Movie. This analysis describes the multiple personalities which occur in Eddie Brock as the main character of the movie. The data are obtained from the script of the movie which is analyzed in discussion of this study. The writers adopts the theory of multiple personality with a concept of disruption in memory and identity of a person. Multiple personality is also termed Dissociative Identity Disorder, disorder marked by the change of individual feeling concerning identity, memory or conscious. An individual gets difficulty in recollecting important events of himself in the past, forgetting his identity even forming his new identity. The whole study is conducted by descriptive qualitative design, classifying the obtained data in two sub topics. The first is about the main  cahracter as a journalist. The second is about the main character as  venom. As a journalist, he is weak, fearful and kind, but as venom, he is strong, brave and evil. After analyzing the data, it can be concluded that the main character, Eddie Brock. in Venom movie written by Jeff Pinkner Et. Al. has multiple personalities with two personalities.